A prospective study of CSF markers in 250 patients with possible Creutzfeldt–Jakob disease. Issue 9 (21st August 2003) - Van Everbroeck, B; Quoilin, S; Boons, J; Martin, J J; Cras, P
Abstract : Objective: To investigate various cerebrospinal fluid (CSF) markers that could assist in the clinical diagnosis of Creutzfeldt–Jakob disease (CJD). Methods: CSF samples were analysed for the presence of 14-3-3 protein, microtubule associated protein tau, and β amyloid in 250 patients with possible CJD. Densitometric analysis was used to quantify the level of 14-3-3 in all patients. Results: Analysis of the clinical data showed that cerebellar signs or myoclonus combined with progressive dementia were the main features leading to a clinical suspicion of CJD. While 14-3-3 detection had a sensitivity of 100% and a specificity of 92%, tau determination using a threshold of 1300 pg/ml had a sensitivity of 87% and a specificity of 97%. If the protocol for the analysis of 14-3-3 was modified (using densitometric analysis) a higher specificity (97%) could be obtained, but with a lower sensitivity (96%). Maximum sensitivity, specificity, and positive predictive value were obtained with a combination of 14-3-3 and β amyloid determinations. The concentrations of 14-3-3 and tau in the CSF were reduced in CJD patients with a long duration of disease (more than one year; p < 0.05). The concentrations of 14-3-3 or tau were lowest at the onset or at the end stage of the disease, while the β amyloid concentration remained low throughout the course of the disease. Conclusions: Both 14-3-3 and tau protein are sensitive and specific biomarkers for CJD. The combination of 14-3-3 and β amyloid analysis resulted in the maximum sensitivity, specificity, and positive predictive value. When these biomarkers are used in the diagnosis of CJD, the phase of the disease in which the CSF sample was obtained should be taken into account. Disease duration, dependent on the PrP genotype, also has a significant influence on the level of 14-3-3 and tau in the CSF.